Influence of the maternity unit and region of delivery on episiotomy practice in France: a nationwide population‐based study - Julie Cormier; Jade Merrer; Béatrice Blondel; Camille Le Ray (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Our objective was to identify factors associated with episiotomy practice in France, in particular, characteristics of the maternity units and regions of delivery. Material and methods We performed a national cross‐sectional population‐based study in all French maternity units in 2016 including 9284 women with vaginal delivery. Our outcome was the performance of an episiotomy. After stratification for parity, associations of episiotomy practice with individual and organizational characteristics and the region of delivery were estimated with multilevel logistic regression models. The variability in maternity unit episiotomy rates explained by the characteristics studied was estimated by the proportional change in variance. Results A total of 19.9% of the women had an episiotomy. The principal factors associated with episiotomy practice were maternal and obstetric and delivery in a maternity unit with <2000 annual deliveries. After adjusting for individual, obstetric and organizational characteristics, the practice of episiotomy was strongly associated with women's region of delivery. Additionally, women's individual characteristics did not explain the significant variability in episiotomy rates between maternity units (P < 0.001) but maternity unit characteristics partly did (proportion of variance explained: 7.2% for primiparas and 13.6% for multiparas) and regional differences still more (18% and 30.7%, respectively). Conclusions Episiotomy practices in France in 2016 varied strongly between maternity units, largely due to regional differences. Targeted actions by the regional perinatal care networks may reduce the national episiotomy rate and standardize practices.